Synthesis of self-ordered Sb2Te2 films with atomically aligned Te layers and the effect of phonon scattering modulation - Choi, Hyejin; Baeck, Ju Heyuck; Kim, Tae-Hyeon; Song, Jae Yong; Shin, Sangwoo; Cho, HyungHee; Ko, Dae-Hong; Kim, Jin-Sang; Jeong, Kwang Ho; Cho, Mann-Ho (ROYAL SOC CHEMISTRY, 2013)
In this work, we prepared multilayered films with repeated Sb and Te layers by a thermal evaporation method. The film structure was controlled by the layer thickness ratio of Sb to Te, resulting in the formation of self-ordered superlattice structured Sb2Te2/Te films and self-ordered Sb2Te3 films. The thermoelectrical properties and the thermoelectric figure of merit (ZT) closely correlated with the structural characteristics, i.e., the superlattice structure with semiconductor-semimetal layers contributed to both electron and phonon scattering resulting in an improvement in electrical conduction and an increase in phonon scattering. In particular, phonon scattering was significantly increased to further reduce thermal conductivity in the self-ordered superlattice structure of the {Sb2Te2/Te}(n) sample. As a result, a thermoelectric figure of merit of ZT = 1.43 was obtained at 400 K for {Sb(4)Te(6)}(n), indicating that the self-ordered superlattice structure holds great promise as an alternative layered thin film thermoelectric material.
Keywords: ANISOTROPIC THERMOELECTRIC PROPERTIES; LATTICE THERMAL-CONDUCTIVITY; THIN-FILMS; PERFORMANCE; REDUCTION